The influence of songs and games in the english foreign language in the learning motivation of kindergarten children in Ecuador. - Mariscal, Laura; Gaibor Zabala, Jenny; Sotomayor Torres, Sebastián (SATHIRI, 2020)
This study intends to show the incidence of the use of songs and games on pre-scholar children’s learning motivation in an English class in Ecuador. The study was based on a mixed design method with quantitative and qualitative research which was done through bibliographical, field, and descriptive research. A team of three researchers carried out an observation of 154 children from 3 to 5 years old, interviewed some teachers and the institution coordinator of the English department. The teachers from the institution controlled the level of incidence with the children when they were exposed to the songs and games by using a checklist. The final results showed that games and songs have a positive effect on the learning motivation of this language regardless of achieving recognition and increase of vocabulary. Participants were affected regarding interaction and active participation which is directly related to the children’s cognitive and social development. Consequently, these two tools should not be considered merely as entertainment ones but rather as methodological and didactic strategies, especially in the teaching of vocabulary.
Keywords: learning; songs; kindergarden; games; motivation